2019
DOI: 10.1039/c9me00024k
|View full text |Cite
|
Sign up to set email alerts
|

Charge-tunable graphene dispersions in water made with amphoteric pyrene derivatives

Abstract: Pyrene derivatives with biomolecular functional groups (lysine and taurine) have been used to produce stable, concentrated and biocompatible graphene dispersions with amphoteric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
(91 reference statements)
1
11
0
Order By: Relevance
“…AFM results show that the average flake size of the two BPS dispersions is centered at ~125 nm, slightly smaller than that of the flakes in the MPS dispersion, which is peaked at ~230 nm, in agreement with previous studies reporting graphene dispersions prepared with pyrene derivatives. 4,11,21,29 The average flake size of the two supernatant dispersions obtained with BPS was about ~50 nm, which is expected, as smaller and thinner flakes are likely to be found in the supernatant. Note that with traditional pyrene derivatives, the concentration of graphene in the supernatant is too small, typically below 0.01 mg/mL, for further use; in contrast, LPE with BPS offers a very simple way to achieve concentrated and enriched graphene dispersions, although of much reduced flake size.…”
Section: Liquid-phase Exfoliationmentioning
confidence: 73%
See 1 more Smart Citation
“…AFM results show that the average flake size of the two BPS dispersions is centered at ~125 nm, slightly smaller than that of the flakes in the MPS dispersion, which is peaked at ~230 nm, in agreement with previous studies reporting graphene dispersions prepared with pyrene derivatives. 4,11,21,29 The average flake size of the two supernatant dispersions obtained with BPS was about ~50 nm, which is expected, as smaller and thinner flakes are likely to be found in the supernatant. Note that with traditional pyrene derivatives, the concentration of graphene in the supernatant is too small, typically below 0.01 mg/mL, for further use; in contrast, LPE with BPS offers a very simple way to achieve concentrated and enriched graphene dispersions, although of much reduced flake size.…”
Section: Liquid-phase Exfoliationmentioning
confidence: 73%
“…Natural graphite crystals were provided by Graphexel Ltd. Graphene dispersions were prepared by LPE in water following the protocol developed in previous works. 4,21,29 In detail, 300 mg of graphite and varying amount of stabilisers wereadded to 100 mL of de-ionized (DI) water. The mixture was then sonicated at 600W for 7 days using a Hilsonic bath sonicator.…”
Section: Preparations Of Graphene Dispersionsmentioning
confidence: 99%
“…Graphene dispersions were prepared via LPE in water following the protocol developed in previous works. 22,25,28 In detail, 30 mg of graphite was added to 10 mL of de-ionised (DI) water, previously mixed with 4 mg of the cationic pyrenes. The mixture was then sonicated at 300 W for 7 days using a Hilsonic bath sonicator.…”
Section: Preparation Of Graphene Dispersionsmentioning
confidence: 99%
“…[21][22][23] Only a few studies have reported exfoliation with cationic pyrene molecules, resulting in poorly concentrated and/or unstable graphene dispersions, hindering their use in practical applications. 21,26,27 Amphoteric pyrene molecules were also recently used to produce graphene dispersions, 28 but their reduced colloidal stability at neutral pH makes this material unsuitable for most applications. One of the major bottlenecks of LPE in water assisted by pyrene derivatives is related to the poor understanding of the nanoscale mechanisms giving rise to exfoliation and stabilisation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…9 Among these techniques, liquid phase exfoliation offers a simple and low-cost approach, compatible with large area deposition methods. 10,11 Graphene can be synthesized by liquid phase exfoliation using organic solvents [12][13][14] or stabilizers in water solutions, [15][16][17][18][19][20] and can be thus further exploited in printable electronic applications.…”
Section: Introductionmentioning
confidence: 99%